Accumulation of terpenoid phytoalexins in maize roots is associated with drought tolerance. (23rd January 2015) - Vaughan, Martha M.; Christensen, Shawn; Schmelz, Eric A.; Huffaker, Alisa; Mcauslane, Heather J.; Alborn, Hans T.; Romero, Maritza; Allen, Leon Hartwell; Teal, Peter E. A.
Abstract: Maize ( Z ea mays ) production, which is of global agro‐economic importance, is largely limited by herbivore pests, pathogens and environmental conditions, such as drought. Zealexins and kauralexins belong to two recently identified families of acidic terpenoid phytoalexins in maize that mediate defence against both pathogen and insect attacks in aboveground tissues. However, little is known about their function in belowground organs and their potential to counter abiotic stress. In this study, we show that zealexins and kauralexins accumulate in roots in response to both biotic and abiotic stress including, D iabrotica balteata herbivory, F usarium verticillioides infection, drought and high salinity. We find that the quantity of drought‐induced phytoalexins is positively correlated with the root‐to‐shoot ratio of different maize varieties, and further demonstrate that mutant an2 plants deficient in kauralexin production are more sensitive to drought. The induction of phytoalexins in response to drought is root specific and does not influence phytoalexin levels aboveground; however, the accumulation of phytoalexins in one tissue may influence the induction capacity of other tissues. Abstract : Terpenoid phytoalexins accumulate in maize roots with D iabrotica balteata herbivory, F usarium verticillioides infection, drought and high salinity. Mutant an2 plants deficient in kauralexin biosynthesis are more sensitive to drought. Commentary: Small molecules with big impact: terpenoid phytoalexins as key factors in maize stress tolerance